Pre-notification Parcel Tracking System - Loke Chin Soon; Mohamad, Shamsul (Evolution in Electrical and Electronic Engineering, 2021)
Nowadays, the goods tracking system is becoming more and more important due to the rise of online shopping. It is very convenient to buy online as users only need to relax and press some buttons to buy the goods they want. The trend of online shopping increases drastically, especially during these few months due to the rise of coronavirus. In order to provide a better service to the customer, most online shopping platforms cooperate with courier services to provide a better preferential to customers. Hence, a pre-notification parcel tracking system is created so that customers can obtain the latest host location using this system. This paper aims to accomplish the objectives where the customer can obtain the latest host location by using the GPS service on Android devices. The user and host application were created using Android Studio, and the Firebase Realtime Database is used as the database for this system. As a result, the GPS obtained for both applications is highly accurate. The host location is updated to the database when there are chances for the host location while the user application obtained the latest host location from the database. The tracking application also able to record and update the parcel information for future reference.